Obstructive Tracheal Necrosis in a Dog Secondary to Smoke Inhalation Injury—Case Report - Rosati, Tommaso; Burkitt, Jamie M.; Watson, Katherine D.; Jandrey, Karl E.; Osborne, Laura G.; Sinnott, Devinn M.; Epstein, Steven E. (Frontiers in Veterinary Science, 2020)
A 4-year-old Siberian Husky mix was referred to the emergency service of the University of California Davis Veterinary Medical Teaching Hospital after being found unconscious in a housefire. Upon arrival, the dog was conscious and panting with normal breathing effort. The dog was initially treated with oxygen therapy to minimize the risk of carbon monoxide toxicosis. Progressive agitation with paroxysmal episodes of increased respiratory effort and increased upper airway sounds were noted approximately 48 hours after presentation. Hypoxemia was then documented. Clinical signs continued to progress despite supportive measures, and five days after initial presentation mechanical ventilation was deemed indicated. Following anesthetic induction, endotracheal intubation was performed. Capnography and peak inspiratory pressures recorded on the mechanical ventilator were consistent with airway obstruction. Diffuse intraluminal tracheal obstruction with grossly necrotic tracheal tissue was confirmed using fiber optic tracheoscopy. The patient was humanely euthanized due to grave prognosis. At necropsy, the tracheal lumen was obstructed by sloughed, necrotic tracheal mucosa. This is the first report describing a severe delayed intrathoracic large airway complication secondary to smoke inhalation in a dog.